Modified flame-retardant nanocomposite epoxy powder coating and preparation method thereof
By using functionalized boron nitride nanosheets (BN-AP-E) in epoxy resins, the problem of flammability of traditional epoxy resins is solved, and its flame retardant and mechanical properties are significantly improved, achieving efficient flame retardant and environmentally friendly epoxy powder coatings.
Patent Information
- Application Number
- CN202311409947.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-03-04
AI Technical Summary
Traditional epoxy resins are flammable, limiting their application range, and the inorganic nanofillers are usually low in doses, making it difficult to achieve practical flame retardant levels.
Boron nitride nanosheets (BNNS) were prepared by glucose-assisted ball milling of hexagonal boron nitride (h-BN), and 3-aminopropyltriethoxysilane (APTES) and quaternary tetrapentanol phosphate (PEPA) were grafted onto BNNS through electrostatic action to form hybrid BNNS composites (BN-AP-E), which was then added to epoxy resin to prepare a modified flame retardant nanocomposite epoxy powder coating.
It significantly improves the flame retardant performance of epoxy powder coatings, reduces peak heat release rate (PHRR), increases combustion residue rate, inhibits the release of smoke and toxic gases, and enhances the mechanical properties and heat resistance of the material.
Smart Images

Figure CN119552552A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating preparation, and in particular relates to a modified flame-retardant nano-composite epoxy powder coating and a preparation method thereof. Technical Background
[0002] In recent years, the emission of volatile organic compounds (VOCs) has become an increasingly serious environmental problem, and the development of environmentally friendly coatings has become increasingly important. Powder coatings do not release volatile organic compounds during use and are 100% green powder coatings, which actively respond to the "4E principles" (environment, efficiency, ecology and economy) of the coatings industry. Therefore, the functionalization of powder coatings has received widespread attention. Epoxy resin (EP), as a common thermosetting resin, has excellent mechanical and electrical properties, excellent adhesion and excellent chemical resistance, and is widely used in the field of coatings. However, traditional epoxy resins are flammable, which seriously limits their scope of application. Therefore, the development of environmentally friendly flame retardant fillers to enhance the flame retardant properties of EP is an important research topic.
[0003] Research has found that the flame retardancy, mechanical properties and heat resistance of polymer composites can be improved by adding only a small amount of inorganic nanofillers. Hexagonal boron nitride (h-BN) is a two-dimensional (2D) layered material that can act as a barrier layer during polymer combustion due to its ultra-high temperature stability, high dielectric strength and unique 2D layered structure, preventing the rapid transfer of heat from the polymer and delaying the release of pyrolysis gases. However, the interaction force between B atoms and N atoms in adjacent layers is called lip-lip interaction, which causes h-BN to easily aggregate, seriously affecting the flame retardant efficiency of h-BN and reducing the mechanical properties of polymer nanocomposites. In addition, the introduction dosage of inorganic nanofillers is usually low, which means that practical flame retardancy levels cannot be achieved by h-BN alone.
[0004] At present, the exfoliation and functionalization of h-BN are effective methods to solve the above problems. Fan et al. demonstrated a new method to make boron nitride nanosheets (BNNS) by ball milling in a corrosive sodium hypochlorite solution. Lei et al. obtained amino-modified BNNS by ball milling and adding excess urea (60 times the weight of BN). However, the highly corrosive reagent environment and the large consumption of modifiers greatly increase the safety hazards and overall costs. Wang et al. obtained functionalized BNNS by glucose-assisted ball milling (using 5 times the mass of BN), thereby improving the thermal conductivity and flame retardancy of gelatin composite films. Summary of the invention
[0005] In order to solve the problems existing in the background technology, the present invention provides a modified flame retardant nano composite material epoxy powder coating and a preparation method thereof.
[0006] The present invention specifically adopts the following technical solutions:
[0007] A method for preparing a modified flame-retardant nanocomposite epoxy powder coating comprises the following steps:
[0008] (1) Preparation of BNNS
[0009] D-glucose is dissolved in water to prepare a D-glucose solution; h-BN is then added to the D-glucose solution, and after ultrasonic treatment, it is transferred to an agate jar containing spherical zirconium oxide grinding beads; ball milling is performed, and after the ball milling is completed, the mixture is centrifuged and washed with water to remove unpeeled h-BN flakes; finally, the product is dried in a vacuum oven to obtain BNNS;
[0010] (2) Preparation of BN-AP
[0011] APTES was added to an ethanol-water solution, and the hydrolysis of APTES was completed by ultrasound. Subsequently, BNNS was added to the solution and stirred under heating. Finally, BN-AP was obtained by drying in a vacuum oven.
[0012] (3) Synthesis of BN-AP-E
[0013] Under stirring, BN-AP and PEPA are dispersed in acetonitrile to form a suspension; then, the mixture is stirred under heating and cooled with ice water; finally, it is washed with ethanol and dried in a vacuum oven to obtain BN-AP-E;
[0014] (4) Synthesis of BN-AP-E / EP powder coating
[0015] BN-AP-E, EP, dicyandiamide, 2-methylimidazole, a leveling agent, a defoaming agent, benzoin and silicon micropowder are mixed; then, the mixture is extruded by melt mixing using a twin-screw extruder; after cooling, the extruded flakes are ground and sieved in a high-speed pulverizer; then, the powder is adsorbed onto a workpiece; finally, the spray coating is cured in an oven to obtain a modified flame-retardant nanocomposite epoxy powder coating.
[0016] Furthermore, the method for preparing BNNS in step (1) comprises the following steps:
[0017] 15 g of D-glucose was dissolved in 20 ml of water to prepare a D-glucose solution; then 3 g of h-BN was added to the D-glucose solution, and after ultrasonic treatment for 20 min, it was transferred to an agate jar containing 150 g of spherical zirconia grinding beads; the ball milling process was carried out on a planetary ball mill at a speed of 400 rpm and lasted for 12 h; after the ball milling, the mixture was centrifuged at a speed of 10000 rpm for 10 min and washed with water several times to remove the unpeeled h-BN flakes; finally, the product was dried in a vacuum oven at 60 °C to obtain BNNS.
[0018] Furthermore, the method for preparing BN-AP in step (2) comprises the following steps:
[0019] 0.5 g APTES was added to 100 ml of ethanol-water solution with a volume ratio of 95:5, and ultrasonicated for 20 min to complete the hydrolysis of APTES; then, 10 g BNNS was added to the solution and stirred at 80 °C for 6 h; finally, it was dried in a vacuum oven at 60 °C to obtain BN-AP;
[0020] Furthermore, the synthesis method of BN-AP-E in step (3) comprises the following steps:
[0021] Under mechanical stirring, 1 g of BN-AP and 5 g of PEPA were dispersed in 50 ml of acetonitrile to form a suspension; the mixture was stirred at 60° C. for 6 h and cooled with ice water; finally, it was washed with ethanol and dried in a vacuum oven to obtain BN-AP-E.
[0022] Furthermore, the method for synthesizing the BN-AP-E / EP powder coating in step (3) comprises the following steps:
[0023] BN-AP-E, EP, dicyandiamide, 2-methylimidazole, leveling agent, defoamer, benzoin and silicon micropowder were mixed; the mixture was extruded by melt mixing using a twin-screw extruder at a speed of 35 rpm; after cooling, the extruded flakes were ground in a high-speed crusher and passed through a 160-mesh sieve; then, the powder was adsorbed onto the workpiece using an electrostatic spray gun with an output voltage of 60 kV; finally, the spray coating was cured in an oven at 200°C for 15 minutes to obtain a modified flame-retardant nanocomposite epoxy powder coating.
[0024] Furthermore, the leveling agent is a polyacrylate leveling agent.
[0025] Furthermore, the defoaming agent is a polyether defoaming agent.
[0026] Furthermore, the twin-screw extruder consists of two heating sections, the temperature of the feeding zone is set at 90°C, and the temperature of the extrusion section is set at 100°C.
[0027] Furthermore, the thickness of the sprayed coating is 90±20 μm.
[0028] The present invention has the following beneficial effects:
[0029] 3-Aminopropyltriethoxysilane (APTES) is a widely used silane coupling agent to functionalize particles and improve their compatibility with the matrix.
[0030] Flame retardants composed of phosphorus, nitrogen, silicon and metal-containing compounds can improve the fire safety of EP. 1-Oxophospha-4-hydroxymethyl-2,6,7-trioxabicyclo[2.2.2]octane (PEPA) has a highly symmetrical cage structure and a high phosphate content (17.6%), which has high flame retardancy, especially as a charring agent. In addition, the P atom in the phosphate group can easily produce a P / N synergistic effect with the N atom in the nitrogen compound during combustion.
[0031] The present invention improves the flame retardancy of epoxy resin by functionalizing boron nitride nanosheets with nitrogen-phosphorus synergistic flame retardant (tetrapentyl phosphate, PEPA). Hydroxylated BNNS was obtained by ball milling hexagonal boron nitride (h-BN) with the assistance of glucose. Then, 3-aminopropyltriethoxysilane (APTES) and PEPA were successfully grafted onto BNNS in sequence through electrostatic action to successfully prepare a hybrid BNNS composite material (BN-AP-E). Subsequently, the formed BN-AP-E was added to EP powder coating (BN-AP-E / EP), thereby improving its dispersibility and compatibility in EP powder coating. The results show that the combustion residue of 7.5wt.% BN-AP-E / EP can be as high as 40.10%, and in the cone calorimeter test, the PHRR value is as low as 534.31kW / m 2 , the lowest TSP peak is 5.96, BN-AP-E significantly inhibits the release of smoke and toxicity, and enhances the flame retardancy of epoxy powder coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of the preparation of BN-AP-E and BN-AP-E / EP powder coatings;
[0033] Figure 2 It is the structural representation diagram of BN-AP-E;
[0034] Figure 3 is the XPS characterization diagram of BN-AP-E, where Figure 3 (a) is the XPS high-resolution full spectrum of BN-AP-E; Figure 3 (b) XPS C 1s spectrum of BN-AP-E;
[0035] Figure 3 (c) XPS N 1s spectrum of BN-AP-E; Figure 3 (d) XPS Si 2p spectrum of BN-AP-E;
[0036] Figure 4 This is the SEM characterization image of BN-AP-E;
[0037] Figure 5 TG and DSC characterization diagrams of BN-AP-E / EP;
[0038] Figure 6 This is the cone calorimeter test diagram of BN-AP-E / EP.
[0039] Specific implementation cases
[0040] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.
[0041] 1 Experimental part
[0042] 1.1 Main instruments and reagents
[0043] Ultima IV X-ray diffractometer (Rigaku, Japan), ESCALAB 250Xi X-ray electron spectrometer (Thermo Fisher Scientific, USA), QM-3SP04 planetary ball mill (Nanjing Lebu Technology Industry Co., Ltd.), MF31 scanning electron microscope (Mingmei Optoelectronics Technology Co., Ltd., China), TG 209F3 thermogravimetric analyzer (NETZSCH, Germany), TSK22 twin-screw extruder (Yantai Jiecheng Powder Equipment Co., Ltd.), NICOLET iS10 Fourier transform infrared spectrometer (Thermo Fisher Scientific, USA), QE-400 high-speed pulverizer (Zhejiang Yili Industry and Trade Co., Ltd.), OptiFlex2 electrostatic sprayer (Jinma Coating (Shanghai) Co., Ltd.), DSC214 differential scanning calorimeter (NETZSCH, Germany).
[0044] 1.2 Material preparation method
[0045] 1.2.1 Preparation of BNNS
[0046] The specific steps are as follows: First, 15 g of D-glucose was dissolved in 20 ml of water to prepare a D-glucose solution. Then 3 g of h-BN was added to the D-glucose solution, and after ultrasonic treatment for 20 min, it was transferred to an agate jar containing 150 g of spherical zirconia grinding beads. The ball milling process was carried out on a planetary ball mill at a speed of 400 rpm and lasted for 12 h. After the ball milling, the mixture was centrifuged at 10,000 rpm for 10 min and washed with water several times to remove the unpeeled h-BN flakes. Finally, the product was dried in a vacuum oven at 60 ° C (BNNS). 1.2.2 Preparation of functionalized BNNS (BN-AP).
[0047] 0.5 g APTES (5% of the weight of BNNS) was added to 100 ml of ethanol-water solution with a volume ratio of 95:5, and ultrasonicated for 20 min to complete the hydrolysis of APTES. Subsequently, 10 g BNNS was added to the solution and stirred at 80 ° C for 6 h. Finally, it was dried in a vacuum oven at 60 ° C to obtain APTES functionalized BNNS (BN-AP).
[0048] 1.2.3 Synthesis of BN-AP-E
[0049] BN-AP (1 g) and PEPA (5 g) were dispersed in acetonitrile (50 ml) under vigorous mechanical stirring to form a suspension. Subsequently, the mixture was stirred at 60 °C for 6 h and cooled with ice water. Finally, it was washed several times with ethanol and dried in a vacuum oven to obtain PEPA-functionalized BN-AP (BN-AP-E).
[0050] 1.2.4 Synthesis of BN-AP-E / EP powder coating
[0051] Different amounts of BN-AP-E, EP, dicyandiamide, 2-methylimidazole, leveling agent, defoamer, benzoin, and silicon powder were mixed according to the formula in Table 1. The leveling agent was a polyacrylate leveling agent, and the defoamer was a polyether defoamer. The mixture was extruded by melt mixing using a twin-screw extruder with a rotation speed of 35 rpm. The twin-screw extruder consists of two heating sections, the feeding zone temperature is set to 90°C, and the extrusion section temperature is set to 100°C. After cooling, the extruded flakes are ground in a high-speed crusher and sieved (160 mesh). Subsequently, an electrostatic spray gun with an output voltage of 60kv is used to adsorb the powder onto the workpiece. Finally, the spray coating was cured in an oven at 200°C for 15 minutes, and the coating thickness was 90±20μm. The preparation process of BN-AP-E and BN-AP-E / EP powder coatings is as follows Figure 1 shown.
[0052] Table 1 BN-AP-E, BN-AP-E / EP powder coating formula
[0053]
[0054] 2. Material preparation method
[0055] 2.1 Structural characterization of BN-AP-E
[0056] FTIR is used to characterize the structure of h-BN and its composites, such as Figure 2 a. h-BN at 1394 and 801 cm -1 The surface chemical inertness of the BNNS at 3420 cm -1A new -OH absorption peak appeared at 1060 cm-1, which indicated that the ball-milled BNNS had been successfully hydroxylated at the edge of the BNNS. -1 The characteristic absorption peak corresponding to the stretching vibration of Si-OC appears at . However, since the BN peak is too strong, the signal of the Si-OC group is not obvious. Therefore, the Zeta potential ( Figure 2 c) Functionalization was further confirmed. APTES modification made the BNNS surface positively charged, so that the positively charged BN-AP bound to the negatively charged PEPA through electrostatic interaction. In addition, in the FTIR of BN-AP-E, BN-AP showed a positive charge at 3420 cm -1 The -OH peak at 3394 cm -1 A new peak appeared at , which was attributed to -NH( Figure 2 a).
[0057] XRD determined the crystal structure of h-BN and its composites. Figure 2 As shown in (b), in all samples, the typical diffraction peaks at 26.8°, 41.8°, 44.1°, 55.2° and 76.0° clearly correspond to the (002), (100), (101), (102), (004) and (110) crystal planes of h-BN. In addition, the positions of these diffraction peaks after ball milling and APTES modification are similar, indicating that the modification did not change the crystal structure of h-BN. After PEPA modification, BN-AP-E showed new diffraction peaks at 18.46°, 19.86° and 28.6°, which are consistent with the diffraction peaks of PEPA. All of the above prove the successful preparation of BN-AP-E composite materials.
[0058] 2.2 XPS characterization of BN-AP-E
[0059] To confirm the successful preparation of BN-AP-E, the surface composition of the composite samples was analyzed using XPS. Figure 3 The results in show that BN-AP-E is mainly composed of O, N, C, B, P and Si. Figure 3 As shown in b, the peaks at 284.8 eV, 285.7 eV, 285.0 eV and 286.8 eV in the C1s high-resolution spectrum of BN-AP-E correspond to CC, CN, CO and COP structures, respectively. In addition, the Si 2p high-resolution spectrum of BN-AP-E also shows two Si-OB, Si-C and Si-OH fitting peaks at 102.6 eV, 103.5 eV and 102.1 eV, respectively ( Figure 3d). These fitted peaks indicate that there is a covalent bond between APTES and BNNS. In addition, the N1s high-resolution spectrum of BN-AP-E ( Figure 3 c) shows that the characteristic peaks appearing at 397.9 eV and 398.5 eV correspond to the NB bond and C-NH bond, respectively, which also provides important evidence for the successful modification of BN-AP by PEPA.
[0060] 2.3 SEM characterization of BN-AP-E
[0061] The microstructures of h-BN, BNNS, BN-AP and BN-AP-E were studied by SEM. Figure 4 As shown, in Figure 4 In a, the original h-BN shows a block structure. Figure 4 In b, after ball milling functionalization with D-glucose, BNNSs became smooth and flake-like. Figure 4 In c, several protrusions can be seen attached to the surface of the modified BNNS, which should be APTES attached to BNNS through electrostatic assembly. Figure 4 d is PEPA modified BN-AP. It can be seen in the figure that there are BNNS flakes on the surface of the material, proving that BN-AP-E was successfully prepared.
[0062] TG and DSC characterization of 2.4BN-AP-E / EP
[0063] The thermal stability of composite materials is a very important parameter to describe flame retardancy. TG analysis was performed on EP powder coatings with different BN-AP-E dosages to determine their thermal degradation characteristics under N2 atmosphere. The corresponding TGA and DTG results are shown in Figure 5 Table 2 lists the 5wt.% weight loss (T 5% )、50wt.%weight loss (T 50% ) and the data of the temperature corresponding to the maximum thermal decomposition rate of the material (Tmax). Figure 5 As shown in a, the powder coatings all showed a single degradation process similar to that of pure EP, indicating that the addition of BN-AP-E filler had no effect on the degradation mechanism of the powder coatings. Table 2 shows that the T 5% and T 50% The temperature is lower than that of pure EP powder coating. This phenomenon can be explained by the following two factors.
[0064] h-BN composite materials can form a good mass transfer barrier layer and play a physical barrier role. Secondly, PEPA decomposes into highly dehydratable polyphosphoric acid under heat, thereby reducing T 5%Temperature. Since polyphosphoric acid is not easy to volatilize and has stable chemical properties, it is more suitable for forming a dense carbon layer instead of producing volatile gases. The formed carbon layer in turn improves the thermal stability and the amount of residual carbon in the powder coating. In addition, after adding BN-AP-E, the carbonization rate of the composite material at 800°C reached 41.04%, which proves that BN-AP-E can significantly improve the fire safety of EP powder coatings.
[0065] Table 2 TG data of different contents of BN-AP-E / EP under N2
[0066]
[0067] The glass transition temperature (Tg) is the main indicator of the thermal properties of polymers. The Tg of powder coatings was further determined by DSC. Figure 5 As shown in b, the Tg change of the EP coating containing 7.5wt.% BN-AP-E is the most obvious, which is 6.7℃ higher than that of pure EP.
[0068] Cone calorimeter test of 2.5BN-AP-E / EP
[0069] The heat flux is 35kW / m 2 The combustion performance of the materials was further investigated by Cone Calorimeter Testing (CCT). Figure 6 The curves of heat release rate (HRR), total heat release rate (THR), total smoke generation (TSP) and CO2 generation of EP powder coatings over time are shown in Table 3. Figure 6 As shown in a, the peak heat release rate (PHRR) of pure EP is 590.65kW / m 2 When 5wt.% of BN-AP-E is added to the EP powder coating, the PHRR value increases from 590.65kW / m 2 Reduced to 534.31kW / m 2 When the content of BN-AP-E was increased to 7.5wt%, the PHRR value of BN-AP-E / EP decreased to 503.12kW / m 2 , decreased by 14.8%, while its carbon residue rate increased to 42.10%. In addition, the PHRR time (T PHRR ) was shortened from 59s of pure EP to 43s, indicating that the decomposition time of EP powder coating was accelerated (Table 3). This result is consistent with the TGA analysis results and is attributed to the catalytic decomposition of BN-AP-E.
[0070] Smoke and toxic gases are another leading cause of death in real fires. Figure 6b and 6c show the carbon dioxide production (PCO) and total smoke production (TSP) curves of EP and its composites. The peak carbon dioxide production rate (PCO2) of pure EP is 0.33g / s. After adding BN-AP-E, the PCO2 values of EP powder coatings decreased to varying degrees. The lowest PCO2 value was 0.24g / s, a decrease of 27.3%, while the PCO generation was too low, less than 0.01g / s. In addition, the addition of BN-AP-E significantly inhibited the release of smoke, and the TSP peak values of the corresponding powder coatings were reduced ( Figure 6 c). The lowest TSP peak is 5.96, which is 38.7% lower than that of pure EP.
[0071] THR is also an important parameter for quantifying the size of a fire. Figure 6 d shows the THR curves of EP and its composite materials. The trend of THR is similar to that of HRR. The THR value increases from 52.37 MJ / m 2 Reduced to 34.34MJ / m for 7.5wt.%BN-AP-E / EP 2 , a drop of 34.4%.
[0072] As mentioned above, the optimal dosage for suppressing the thermal emission, toxic gas and smoke release of EP powder coatings is 7.5wt.% BN-AP-E. As a two-dimensional nanohybrid, BN-AP-E can play a physical barrier role, reducing heat and mass transfer during the combustion of EP powder coatings, thereby reducing the fire hazard.
[0073] Table 3 Related data of cone calorimeter test of BN-AP-E / EP with different contents
[0074]
Claims
1. A method for preparing a modified flame retardant nanocomposite epoxy powder coating, characterized in that: The following steps are involved: (1) Preparation of BNNS D-glucose is dissolved in water to prepare a D-glucose solution; h-BN is then added to the D-glucose solution, and after ultrasonic treatment, it is transferred to an agate jar containing spherical zirconium oxide grinding beads; ball milling is performed, and after the ball milling is completed, the mixture is centrifuged and washed with water to remove unpeeled h-BN flakes; finally, the product is dried in a vacuum oven to obtain BNNS; (2) Preparation of BN-AP APTES was added to an ethanol-water solution, and the hydrolysis of APTES was completed by ultrasound. Subsequently, BNNS was added to the solution and stirred under heating. Finally, BN-AP was obtained by drying in a vacuum oven. (3) Synthesis of BN-AP-E Under stirring, BN-AP and PEPA are dispersed in acetonitrile to form a suspension; the mixture is stirred under heating and cooled with ice water; finally, it is washed with ethanol and dried in a vacuum oven to obtain BN-AP-E; (4) Synthesis of BN-AP-E / EP powder coating BN-AP-E, EP, dicyandiamide, 2-methylimidazole, a leveling agent, a defoaming agent, benzoin and silicon micropowder are mixed; the mixture is extruded by melt mixing using a twin-screw extruder; after cooling, the extruded flakes are ground and sieved in a high-speed pulverizer; then, the powder is adsorbed onto a workpiece; finally, the spray coating is cured in an oven to obtain a modified flame retardant nanocomposite epoxy powder coating.
2. The method for preparing the modified flame retardant nanocomposite epoxy powder coating according to claim 1, characterized in that: The method for preparing BNNS in step (1) comprises the following steps: 15 g of D-glucose was dissolved in 20 ml of water to prepare a D-glucose solution; then 3 h-BN was added to the D-glucose solution, and after ultrasonication for 20 min, it was transferred to an agate jar containing 150 g of spherical zirconia grinding beads; the ball milling process was carried out on a planetary ball mill at a speed of 400 rpm and lasted for 12 h; after the ball milling, the mixture was centrifuged at a speed of 10,000 rpm for 10 min and washed with water several times to remove the unpeeled h-BN flakes; finally, the product was dried in a vacuum oven at 60 ° C to obtain BNNS.
3. The method for preparing the modified flame retardant nanocomposite epoxy powder coating according to claim 1, characterized in that: The method for preparing BN-AP in step (2) comprises the following steps: 0.5 g APTES was added to 100 ml of ethanol-water solution with a volume ratio of 95:5, and ultrasonication was performed for 20 min to complete the hydrolysis of APTES; then, 10 g BNNS was added to the solution and stirred at 80 °C for 6 h; finally, it was dried in a vacuum oven at 60 °C to obtain BN-AP.
4. The method for preparing the modified flame retardant nanocomposite epoxy powder coating according to claim 1, characterized in that: The synthesis method of BN-AP-E in step (3) comprises the following steps: Under mechanical stirring, 1 g of BN-AP and 5 g of PEPA were dispersed in 50 ml of acetonitrile to form a suspension; then, the mixture was stirred at 60 °C for 6 h and cooled with ice water; finally, it was washed with ethanol and dried in a vacuum oven to obtain BN-AP-E.
5. The method for preparing the modified flame retardant nanocomposite epoxy powder coating according to claim 1, characterized in that: The method for synthesizing the BN-AP-E / EP powder coating in step (3) comprises the following steps: BN-AP-E, EP, dicyandiamide, 2-methylimidazole, leveling agent, defoamer, benzoin and silicon micropowder were mixed; the mixture was extruded by melt mixing using a twin-screw extruder at a speed of 35 rpm; after cooling, the extruded flakes were ground in a high-speed crusher and passed through a 160-mesh sieve; the powder was adsorbed onto the workpiece using an electrostatic spray gun with an output voltage of 60 kV; finally, the spray coating was cured in an oven at 200°C for 15 minutes to obtain a modified flame-retardant nanocomposite epoxy powder coating.
6. The method for preparing the modified flame retardant nanocomposite epoxy powder coating according to claim 5, characterized in that: The leveling agent is a polyacrylate leveling agent.
7. The method for preparing the modified flame-retardant nanocomposite epoxy powder coating according to claim 5, characterized in that: The defoamer is a polyether defoamer.
8. The method for preparing the modified flame-retardant nanocomposite epoxy powder coating according to claim 5, characterized in that: The twin-screw extruder consisted of two heating sections, with the temperature of the feeding zone set at 90 °C and the temperature of the extrusion section set at 100 °C.
9. The method for preparing the modified flame-retardant nanocomposite epoxy powder coating according to claim 5, characterized in that: The thickness of the sprayed coating is 90±20 μm.
10. A modified flame retardant nanocomposite epoxy powder coating prepared according to the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Flame-retardant polyolefin macromolecule composite material and preparation method thereof
CN110172178A
Preparation method of modified hexagonal boron nitride flame retardant and water-based intumescent fire-retardant coating
CN110343291A
High-dispersion amorphous carbon coated hexagonal boron nitride nanosheet and preparation method thereof
CN112662449A
Nano powder coating as well as preparation method and application thereof
CN114574072A